Healing through the Bones: Empowerment and the Process of Exhumations in the Context of Cyprus. - Fics, Kristian T. P. (Hamilton Books (R and L) : Hamilton Books, 2016)
This study explores an effect of violent conflict in Cyprus-Missing Persons-and the process of exhumations. By interviewing experts on the Cypriot conflict about the exhumations process, Fics has revealed the challenges and successes that may arise for sustainable peace and healing in Cyprus and beyond.